2004
DOI: 10.1242/jcs.01163
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced podocalyxin expression alters the structure of podocyte basal surface

Abstract: Glomerular basement membrane (GBM) and podocalyxin are essential for podocyte morphology. We provide evidence of functional interconnections between basement membrane components (collagen IV and laminin), the expression of podocalyxin and the morphology of human glomerular epithelial cells (podocytes). We demonstrated that GBM and laminin, but not collagen IV, up-regulated the expression of podocalyxin. Scanning electron microscopy revealed that laminin induced a modified morphology of podocytes with process f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 51 publications
2
51
0
1
Order By: Relevance
“…AKAP12 has been reported to inhibit angiogenesis and promote tight-junction formation in blood-brain barrier. 21 hPODXL encodes a sialomucin protein that regulates cell adhesion in podocyte 22 and tumor, 23 and is expressed in endothelial cells and bind to L-selectin. 24 It has also been reported that AKAP12 is expressed strongly in subconfluent, and only weakly in confluent, endothelial cell cultures, a pattern opposite to that of HSPA12B.…”
Section: Discussionmentioning
confidence: 99%
“…AKAP12 has been reported to inhibit angiogenesis and promote tight-junction formation in blood-brain barrier. 21 hPODXL encodes a sialomucin protein that regulates cell adhesion in podocyte 22 and tumor, 23 and is expressed in endothelial cells and bind to L-selectin. 24 It has also been reported that AKAP12 is expressed strongly in subconfluent, and only weakly in confluent, endothelial cell cultures, a pattern opposite to that of HSPA12B.…”
Section: Discussionmentioning
confidence: 99%
“…40,41 Podocalyxin first appears just before formation of foot processes and slit pores, and its redistribution correlates with that of junctions: It is expressed as junctional proteins migrate basolaterally and is always found along the apical surface of podocyte cell bodies and foot processes above the level of slit diaphragms. 1,40 -42 Maintenance of the intricate glomerular podocyte architecture is essential for optimal filtration; numerous human diseases and animal models of glomerular malfunction involve loss of structural integrity, 43 a phenotype often attributed to abnormal podocalyxin. Diabetic nephropathy, a leading cause of chronic kidney failure and ESRD, involves broadening of foot processes and is accompanied by a decrease in glomerular sialic acid content; loss of foot process structure is also the main morphologic abnormality in patients with nephrotic syndrome.…”
Section: Diverse Roles Of Podocalyxin In a Variety Of Tissuesmentioning
confidence: 99%
“…Luminal podocytic membrane possesses negative surface charge maintained mainly by podocalyxin (PC), the latter regulating podocyte morphology, as well as foot process formation and maintenance [4,5]. Glucose induces PC suppression in glomeruli of streptozotocin- diabetic rats in vivo [6], and in human glomerular epithelial cells (HGEC) in vitro [5,7]. Suppressed PC expression, in HGEC, could not be restored by reverting glucose concentration to normal levels for either short or longer time intervals [7].…”
Section: Introductionmentioning
confidence: 99%
“…The phenotype of HGEC fully agrees with parental podocytes, since they express visceral glomerular epithelial cell markers such as PC, CALLA, cytokeratin, α3β1 integrin, α1 and α5 chains of collagen IV and WT1. Moreover, HGEC have already been used for studies of expression and function [5,7]. …”
Section: Introductionmentioning
confidence: 99%